Sharing Lessons From Successes: Long-term Care Facilities That Weathered the Storm of COVID-19 and Staffing Crises. Issue 1 (26th January 2023) - Martin, Nicky; Frank, Barbara; Farrell, David; Brady, Cathie; Dixon-Hall, Janice; Mueller, Jessica; Rantz, Marilyn
Abstract : Purpose: To identify leadership styles and staffing strategies in Missouri long-term care (LTC) facilities that stood out among their peers as "positive deviants" with regard to COVID-19 infections and staffing shortages. Methods: Statewide survey of all LTC facilities to identify exemplar facilities with stable staffing and low rates of COVID-19. Interviews with senior leaders were conducted in 10 facilities in the state to understand the strategies employed that led to these "positive outliers." A result-based educational program was designed to describe their actions and staff reactions. Results: Exemplar leaders used transformational leadership style. Top reasons for their success were as follows: (1) trusting and supportive staff relationships; (2) positive presence and communication; and (3) use of consistent staffing assignments. Strong statewide participation was noted in the educational programs.